1982
DOI: 10.1007/bf02242150
|View full text |Cite
|
Sign up to set email alerts
|

Fascioliasis in beef cattle in north-west Argentina

Abstract: Two thousand and ninety beef cattle livers from north-west Argentina were inspected at a large slaughterhouse in Salta; 13% were found to have lesions of fascioliasis and these were classified according to their severity. Of the livers condemned 182 (67.2%) were lightly affected, 77 (28.4%) moderately affected and only 12 (4.4%) severely affected. In a field survey 85 animals, mainly between 6 and 18 months old, were slaughtered and 12 (14%) had lesions of fascioliasis. The influence of Fasciola hepatica on we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 4 publications
0
7
1
Order By: Relevance
“…These variations may be due to epidemiology of Fasciola spp, study area, and study design. Our results are different from [42,43] .The highest prevalence in poor condition animals might be due to chronic disease and concurrent infection enhance the susceptibility of fasciolosis. As a result excessive weight loss was observed in those cattle suffering from fasciolosis and the most common sign was loss of weight [16,29].…”
Section: Discussioncontrasting
confidence: 93%
“…These variations may be due to epidemiology of Fasciola spp, study area, and study design. Our results are different from [42,43] .The highest prevalence in poor condition animals might be due to chronic disease and concurrent infection enhance the susceptibility of fasciolosis. As a result excessive weight loss was observed in those cattle suffering from fasciolosis and the most common sign was loss of weight [16,29].…”
Section: Discussioncontrasting
confidence: 93%
“…The presence of F. hepatica eggs in the faeces reveals that mature flukes are located in the bile ducts and/or the gall-bladder. Most of the epidemiological studies on fasciolosis have been carried out by coproscopic analysis (Dwinger et al 1982;Boulard et al 1985;Bouvry and Rau 1986). Nevertheless, it has to be considered that coprological methods cannot detect fasciolosis until 8-12 weeks after infection, when most of the pathological lesions have been formed (Jemli et al 1992;Almazan et al 2001).…”
Section: Resultsmentioning
confidence: 97%
“…According to Dwinger et al (1982) and Yilma and Mesfin (2000), the number of fluke has no direct relationship with the liver gross lesion as it was observed that relatively less flukes in severely affected livers of beef cattle.…”
Section: Discussionmentioning
confidence: 99%
“…However, severe fibrosis impedes the passage of immature flukes and acquired resistance and calcification of bile ducts that impaired the further passage of young flukes and play a role by creating unfavorable microenvironment which results in the expulsion of flukes (Dwinger et al, 1982;Ramato, 1992).…”
Section: Discussionmentioning
confidence: 99%